2008
DOI: 10.1111/j.1745-7254.2008.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1 protects mesenchymal stem cells against serum deprivation and hypoxia-induced apoptosis through the PI3KAkt pathway1

Abstract: Aim: The angiopoietin-1 (Ang1)/Tie-2 signaling system not only plays a pivotal role in vessel growth, remodeling, and maturation, but also reduces apoptosis of endothelial cells, neurons, and cardiomyocytes. However, relatively little is known as to whether Ang1 has a protective effect on mesenchymal stem cells (MSC). The aim of the present study was to investigate the protective effect of Ang1/Tie-2 signaling on MSC against serum deprivation and hypoxia-induced apoptosis, and to determine the possible mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 34 publications
(47 reference statements)
6
33
0
1
Order By: Relevance
“…The effects on MAPK signaling were not through elements of the feedback loop as previously reported, 18 but rather through the upstream regulators of MAPK signaling such as angiopoietin 1 and midkine, which are upregulated in cells with chondrogenic potential. These transcripts may have a role not only in the maintenance of the chondrogenic potential but also in the overall physiology of hMSCs; angiopoietin 1 has been implicated in the paracrine tissue repair activity displayed by MSCs [45][46][47] and as an antiapoptotic factor 48 ; secreted frizzledrelated protein 1 has also been reported to play a role in the tissue repair activity of MSCs 49,50 and in controlling osteogenic differentiation. [51][52][53] Additionally, a recent report indicates that six transmembrane epithelial antigen of the prostate 1, also upregulated in cells with chondrogenic potential, may be a marker for MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The effects on MAPK signaling were not through elements of the feedback loop as previously reported, 18 but rather through the upstream regulators of MAPK signaling such as angiopoietin 1 and midkine, which are upregulated in cells with chondrogenic potential. These transcripts may have a role not only in the maintenance of the chondrogenic potential but also in the overall physiology of hMSCs; angiopoietin 1 has been implicated in the paracrine tissue repair activity displayed by MSCs [45][46][47] and as an antiapoptotic factor 48 ; secreted frizzledrelated protein 1 has also been reported to play a role in the tissue repair activity of MSCs 49,50 and in controlling osteogenic differentiation. [51][52][53] Additionally, a recent report indicates that six transmembrane epithelial antigen of the prostate 1, also upregulated in cells with chondrogenic potential, may be a marker for MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although these The MSC-secreted factors seem to have more than just proangiogenic effects; MSC treatment reduces the lacking (13). Instead of MSC-derived regeneration of the heart, researchers have shown a fusion event of apoptotic index within the peri-infarct area (37,68). In vitro, cultured cardiomyocytes have improved survival MSCs with injured cardiomyocytes (4).…”
Section: [Nkx25] and Mef-2c Providing Insight Into The Myocardial Imentioning
confidence: 99%
“…It has also been demonstrated that preconditioning MSCs with stromal-derived factor 1α (SDF-1α) alone or in combination with growth factors such as fibroblast growth factor-2, insulin-like growth factor-1, and bone morphogenetic protein-2 can alleviate the host cell apoptosis and enhance their therapeutic effects (Mias et al, 2008). Our previous studies have shown that some candidates for preconditioning, such as heregulin (Mias et al, 2008), cyclosporin A (Chen et al, 2008), angiopoietin-1 (Liu et al, 2008), and dimethyloxalylglycine (DMOG) (Liu et al, 2009b), can protect MSCs against hypoxia and serum deprivation-induced apoptosis through classic cytoplasmic and/or mitochondrial apoptotic pathways.…”
Section: Discussionmentioning
confidence: 99%